2015
DOI: 10.1186/s12934-015-0234-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased production of inosine and guanosine by means of metabolic engineering of the purine pathway in Ashbya gossypii

Abstract: BackgroundInosine and guanosine monophosphate nucleotides are convenient sources of the umami flavor, with attributed beneficial health effects that have renewed commercial interest in nucleotide fermentations. Accordingly, several bacterial strains that excrete high levels of inosine and guanosine nucleosides are currently used in the food industry for this purpose.ResultsIn the present study, we show that the filamentous fungus Ashbya gossypii, a natural riboflavin overproducer, excretes high amounts of inos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…Physiological GMP inhibition has been also questioned for the E. coli enzyme (Pimkin and Markham 2008). Moreover, we have recently determined that, in the wild-type A. gossypii A4 strain, the intracellular concentrations of XMP are about 8 times higher than those of GMP and about 40 times larger than IMP (Ledesma-Amaro et al 2015), further supporting the hypothesis that XMP-rather than GMP-feedback inhibition might be a main regulator of IMPDH activity in vivo. Therefore, by solving the highresolution crystallographic structures in complex with IMP and XMP, we have settled a reliable basis for computational modeling as well as protein engineering strategies towards enzyme optimization and/or product inhibition removal which we are at present developing in our laboratory.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Physiological GMP inhibition has been also questioned for the E. coli enzyme (Pimkin and Markham 2008). Moreover, we have recently determined that, in the wild-type A. gossypii A4 strain, the intracellular concentrations of XMP are about 8 times higher than those of GMP and about 40 times larger than IMP (Ledesma-Amaro et al 2015), further supporting the hypothesis that XMP-rather than GMP-feedback inhibition might be a main regulator of IMPDH activity in vivo. Therefore, by solving the highresolution crystallographic structures in complex with IMP and XMP, we have settled a reliable basis for computational modeling as well as protein engineering strategies towards enzyme optimization and/or product inhibition removal which we are at present developing in our laboratory.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, we also studied the production of the nucleosides guanosine and inosine, given their interest as precursors of the foodstuff additives IMP and GMP with flavoring, nutritional and pharmaceutical properties (Ledesma-Amaro et al 2013). To this respect, we have recently shown that both nucleosides are excreted to the extracellular media of A. gossypii's flask fermentations at milligrams-per-liter levels and have proposed this fungus as a promising candidate for nucleoside industrial production (Ledesma-Amaro et al 2015). Given that overexpression of IMPDH causes the disruption of the STE12 locus (by the insertion of the P-GPD -IMPDH construct), we previously demonstrated that the disruption of STE12 does not affect inosine, guanosine, riboflavin production, or growth rate (Table S2 in the Supplementary Material).…”
Section: Impdh Activity Significantly Influences Metabolite Productiomentioning
confidence: 99%
See 1 more Smart Citation
“…GTP, the other riboflavin precursor, is synthesized through the purine pathway, which starts with the formation of phosphoribosyl pyrophosphate (PRPP) from ribose 5-P and ATP. Interestingly, A. gossypii was recently shown to secrete high amounts of inosine and guanosine, which are purine nucleosides produced via this same pathway (Ledesma-Amaro et al, 2015). PRPP is not only required for the de novo and salvage pathways of purine, pyrimidine and pyridine (NAD + , NADP + ) nucleotides, but also as a precursor of histidine ( Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, since the beginning of this decade, we have witnessed the increasingly stronger shift of the A. gossypii biotechnological paradigm from riboflavin to other commercially interesting high-value compounds, such as recombinant proteins (Ribeiro et al, 2010), single cell oil (SCO; Ledesma-Amaro et al, 2014a) and flavour compounds (Ravasio et al, 2014;Ledesma-Amaro et al, 2015). In this review, we will focus on the emerging biotechnological potential of this promising cell factory that nowadays goes far beyond riboflavin production ( Fig.…”
Section: Introductionmentioning
confidence: 99%